Collaborative Referral Model for Hepatitis C Screening and Treatment in a Remote Mountainous Region of Taiwan during the COVID-19 Pandemic - Chi-Ming Tai; Ming-Jong Bair; Tzu-Haw Chen; Cheng-Hao Tseng; Chih-Cheng Chen; Hung Lam; Ming-Lung Yu (Viruses, 2023)
Community-based screening for the hepatitis C virus (HCV) decreased during the COVID-19 pandemic. We developed a collaborative referral model between a primary clinic (Liouguei District Public Health Center, LDPHC) and a tertiary referral center to increase HCV screening and treatment uptake in a mountainous region of Taiwan. Once-in-a-lifetime hepatitis B and C screening services established by the Taiwan National Health Insurance were performed at LDPHC. Antibody-to-HCV (anti-HCV)-seropositive patients received scheduled referrals and took a shuttle bus to E-Da hospital for HCV RNA testing on their first visit. Direct-acting antiviral agents (DAAs) were prescribed for HCV-viremic patients on their second visit. From October 2020 to September 2022, of 3835 residents eligible for HCV screening in Liouguei District, 1879 (49%) received anti-HCV testing at LDPHC. The overall HCV screening coverage rate increased from 40% before referral to 69.4% after referral. Of the 79 anti-HCV-seropositive patients, 70 (88.6%) were successfully referred. Of the 38 HCV-viremic patients, 35 (92.1%) received DAA therapy, and 32 (91.4%) achieved sustained virological response. The collaborative referral model demonstrates a good model for HCV screening and access to care and treatment in a Taiwan mountainous region, even during the COVID-19 pandemic. Sustained referral is possible using this routine referral model.